MANAJEMEN RESIKO DAN RESIKO DALAM ISLAM - Fasiha Kamal (MUAMALAH, 2014)
Uncertainties and risks may start at the beginning of human existence. Dependence of man by man to explain the future, such as when a human wants unsurpassable determines the future, then people predict the future with some of the possibilities, then create a dependency to the astrologer, priest, pastor and others. Thus risk management has been applied in people's lives over time,. Islamic Perspective in risk management can be studied from a organsiasi story of Joseph in a dream mentakwilkan king at that time. This story is contained in the Quran